Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5cp03844h
|View full text |Cite
|
Sign up to set email alerts
|

Combined near-infrared excited SEHRS and SERS spectra of pH sensors using silver nanostructures

Abstract: Surface-enhanced hyper-Raman scattering (SEHRS) and surface-enhanced Raman scattering (SERS) of para-mercaptobenzoic acid (pMBA) were studied with an excitation wavelength of 1064 nm, using different silver nanostructures as substrates for both SEHRS and SERS. The spectra acquired for different pH values between pH 2 and pH 12 were compared with SERS data obtained from the identical samples at 532 nm excitation. Comparison of the ratios of the enhancement factors from SEHRS and SERS experiments with those from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 49 publications
3
82
0
Order By: Relevance
“…Figure 2A-d shows the typical SERS spectra collected using 830 nm cw excitation (3 mW) in the endosomal compartments with different pH value. This study demonstrated pH imaging in single live cells at subendosomal resolution using SERS pH sensors is feasible [81]. Kneipp's group did a further research to monitor changes in local pH of the cellular compartments of living NIH/3T3 cells [87] and found that SERS nanosensors could dynamically monitor the change of local pH in individual live cells to be followed at subendosomal resolution in a timeline of cellular processes.…”
Section: Monitoring Phmentioning
confidence: 99%
“…Figure 2A-d shows the typical SERS spectra collected using 830 nm cw excitation (3 mW) in the endosomal compartments with different pH value. This study demonstrated pH imaging in single live cells at subendosomal resolution using SERS pH sensors is feasible [81]. Kneipp's group did a further research to monitor changes in local pH of the cellular compartments of living NIH/3T3 cells [87] and found that SERS nanosensors could dynamically monitor the change of local pH in individual live cells to be followed at subendosomal resolution in a timeline of cellular processes.…”
Section: Monitoring Phmentioning
confidence: 99%
“…next section). 22,44 In the SERS and SEHRS spectra, the scattering powers P SERS and P SEHRS , respectively, are…”
Section: Understanding the Overall Sehrs Enhancement In Experimentsmentioning
confidence: 99%
“…Such estimations were made to, e.g., explain the origin of the difference between the SERS and SEHRS enhancement factors for non-resonant spectra of the dye crystal violet 44 and for para-mercaptobenzoic acid ( pMBA). 22 In analogy to the empirical relationship between the electromagnetic SERS enhancement factor and the surface plasmon absorption spectrum, …”
Section: Understanding the Overall Sehrs Enhancement In Experimentsmentioning
confidence: 99%
See 2 more Smart Citations